PENGARUH BUDAYA ORGANISASI DAN PERILAKU BIROKRASI TERHADAP EFEKTIVITAS ORGANISASI: STUDI PADA DINAS-DINAS, BADAN-BADAN, KANTOR-KANTOR DAN SEKRETARIAT DI KABUPATEN SUMEDANG - Mulyaningsih (PAPATUNG: Jurnal Ilmu Administrasi Publik, Pemerintahan dan Politik, 2019)
The purpose of this study was to determine the effect of organizational culture and bureaucratic behavior on organizational effectiveness in the Dinas-Dinas, Agencies, Offices and Secretariat in Sumedang Regency, both partially and simultaneously. The research method used in this study was a survey by distributing questionnaires to 170 respondents. Analysis of the data used in this study is path analysis to test the research hypothesis. The results of the study prove that there is a positive and significant influence between organizational culture and bureaucratic behavior on organizational effectiveness, both partially and simultaneously.